Analisis Sentimen Opini Publik Mengenai Wajib BPJS Pada Media Sosial Twitter Menggunakan Metode Naïve Bayes - Muhammad Rakha (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
On January 6, 2022, President Joko Widodo signed the Presidential Instruction (Inpres) to the public. One of the points of Presidential Instruction Number 1 of 2022 concerning BPJS as a public service obligation, is a public discussion, concerning applicants for SIMs, STNK marks, and Police Certificates (SKCK) that must accompany BPJS Health membership. Due to the many public complaints about presidential education guidelines, this study was conducted to assess public perceptions using the Naive Bayes algorithm using TF-IDF feature selection. This study uses 362 data which is divided into two classes, positive and negative. The classification process gives the best accuracy results with a percentage of 88.89% using the selection of the TF-IDF function with 90% training data and 10% test data.